Exploring the use and impact of LCA-based information in corporate communications - Molina-Murillo, Sergio A.; Smith, Timothy M. (The international journal of life cycle assessment, 2009)
Background, aim, and scope The effective communication of corporate environmental messages has a history of mixed results and concerns remain around the quality and accurateness of these messages. Life cycle assessment (LCA) information is often presented as a promising informational tool, by which improved communication effectiveness of environmental/sustainable claims may materialize; however, the possibility of information overload has limited its application in marketing communication settings. The overall purpose of this research is to better understand how LCA-based environmental performance information might be effectively communicated in an advertising setting, the impact of such messages on individuals’ attitudes and behavioral intentions, and the mediating roles of informational complexity and credibility. Methods Fictitious, but realistic, advertisements employing LCA-based information were created and tested empirically in two experimental settings. The first, in a business-to-consumer (B2C) setting, examines the influence of several environmental information contents, formats, and disclosures on attitudinal factors toward the ad, brand, and company, as well as behavioral intentions. Using hair shampoo as the product category, and the biodegradability capacity of its bottle as the environmental attribute, regression analyses were developed based on a sample of 3,292 subjects evaluating one of 12 different advertisements. The second experiment presented in this paper expands upon these ideas by focusing on a business-to-business (B2B) environment where the need for cognition, and thus the complexity threshold, is thought to be quite high and where environmental performance is expected to be of importance to the purchaser. This experimental setting includes responses from 1,062 architects and engineers—all of whom are members of the U.S. Green Building Council who evaluated one of eight different advertisements. In this experimental setting, the volume of LCA-based information is varied, while exploring the role of this information in conjunction with functional product performance messages. Results Results indicate that LCA-based information can be effective within an advertising medium in enhancing message credibility, attitudes toward the brand and company, and positively influencing behavioral intentions toward purchasing, even though this information is viewed as complex and detrimental to attitudes toward the advertisement itself. More specifically, results from the first empirical experiment indicate that LCA-based communications make for more poorly reviewed advertising, but the credibility gained through explicit LCA-based environmental disclosures favorably influences the perceptions toward the company and the brand. These results are confirmed in the business-to-business experiment. Evidence from this study suggests that, within environmentally aware and sensitive recipients, advertisements with environmental messages are more effective than those presenting functional product benefits alone, but only when the messages are substantiated with elaborated LCA-based information. Discussion Within the B2C respondents, we found that the perceived complexity of the ad in fact generated a significantly positive attitudinal response concerning the company under evaluation, which was not evident in the B2B study. The results suggest that the end-use consumers in the first experiment more often processed the ad through the peripheral route of persuasion, where the downside risk of presenting complex and detailed environmental information is significant (i.e. people won’t pay attention to the ad), but can be balanced (or even surpassed) by positive associations with presenting additional information (i.e. the company must be strong if it is willing to fully disclose all of this information). Conclusions The influence of perceived complexity of LCA-based advertisements does not appear to negatively influence most measures typically used to assess advertising effectiveness; however, the appeal of the advertisement itself is significantly negatively impacted by increases in complexity. The credibility gained through more elaborated LCA-based environmental messages, to a high extent, compensates the effect of complexity on the attitude toward the appeal of the ad itself. In fact, this credibility strongly influences in a positive manner the attitudes buyers have toward the ad, the brand, the company, and their intention to purchase the product under evaluation. Recommendations and perspectives Practitioners are to reconsider the position that simple and appealing advertisements are most effective to an overall marketing communication strategy addressing environmental performance. Simple messages are often required to gain market awareness and break through the noisy hypermedia marketplace; however, our results suggest that a firm’s ability to gain credibility in its message can compensate for many of the negative effects of highly complex messages. Researchers and LCA professionals influencing methodologies and implementation of LCA at the product level should recognize the potential use of selected and incomplete LCA-based information by firms in marketing communications. While strategic differentiation benefits associated with effective communication of environmental performance may lead to increased use of LCA techniques by firms, appropriate development of standards and certifications may be required to preserve perceptions of objectivity and transparency associated with LCA methodologies.